LECTURERS’ STRATEGIES ON STUDENTS' DISCIPLINE IN CLASSROOM MANAGEMENT DURING ONLINE LEARNING - Wanda Giovani; Ninyikiriza Deborah Lynn; Kristian Anggi Purnomo; Veggi Rische (Journal of Educational Review and Research, 2023)
This study aims to provide an overview of the strategies used by two lecturers at the Catholic University of St. Augustine Hippo in their online classroom management, particularly in disciplining students. The trend of online classes on the St. Augustine Hippo Catholic University campus continues even though the pandemic is over. Online lectures are still being held for several meetings, although not in full. In providing online teaching, lecturers have specific strategies to ensure that the teaching and learning process goes well, one of the criteria is student discipline during the process. The method used to obtain data is in-depth interviews. The results of the in-depth interviews of the two lecturers showed that the challenges in online teaching were bad internet connection, students’ inadequate internet quota, and students’ inactiveness. While the strategies that were used by them in dealing with those problems were giving good example, giving firmness, giving attention, being kind, being affective, and being attentive towards students.